2013
DOI: 10.1103/physrevlett.111.242502
|View full text |Cite
|
Sign up to set email alerts
|

New Fission Fragment Distributions andr-Process Origin of the Rare-Earth Elements

Abstract: Neutron star (NS) merger ejecta offer a viable site for the production of heavy r-process elements with nuclear mass numbers A > ∼ 140. The crucial role of fission recycling is responsible for the robustness of this site against many astrophysical uncertainties, but calculations sensitively depend on nuclear physics. In particular the fission fragment yields determine the creation of 110 < ∼ A < ∼ 170 nuclei. Here we apply a new scission-point model, called SPY, to derive the fission fragment distribution (FFD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
189
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(207 citation statements)
references
References 60 publications
(83 reference statements)
14
189
1
3
Order By: Relevance
“…Also, only ∼ 10% of the final yield came from the termination of the r-process path at N = 212 and Z = 111, while almost 90% of the A ≈ 160 bump shown in Figure 1 was from the fission of more than 200 different parent nuclei mostly via beta-delayed fission. This is in contrast to the yields of [31] that are almost entirely due to a few A ≈ 278 fissioning nuclei with a characteristic four hump FFD. It is important to keep in mind that many microscopic calculations of fission barriers are consistent with an early termination near A ≈ 280.…”
Section: Current Models For the R-processmentioning
confidence: 66%
See 3 more Smart Citations
“…Also, only ∼ 10% of the final yield came from the termination of the r-process path at N = 212 and Z = 111, while almost 90% of the A ≈ 160 bump shown in Figure 1 was from the fission of more than 200 different parent nuclei mostly via beta-delayed fission. This is in contrast to the yields of [31] that are almost entirely due to a few A ≈ 278 fissioning nuclei with a characteristic four hump FFD. It is important to keep in mind that many microscopic calculations of fission barriers are consistent with an early termination near A ≈ 280.…”
Section: Current Models For the R-processmentioning
confidence: 66%
“…Recent studies [29][30][31][32]35] have indicated that the r process in NSMs produces a final abundance pattern that can be similar to the solar r-process abundances, but only for heavier A>130 nuclei.…”
Section: Current Models For the R-processmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, high temperatures and neutron densities enable sequences of successive neutron captures to form nuclei near the neutron drip line which subsequently decay toward stability as the system expands and cools [1,2]. Core collapse supernovae [3] and merging neutron stars [4] are the two leading sites for the rprocess.…”
mentioning
confidence: 99%